(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2023)
Method of automatically determining the carrier frequency, symbol rate, subcarrier separation frequency, manipulation index, and spectrum width of short duration radio signals with binary frequency manipulation are proposed in the article. The method combines four methods of frequency manipulation radio signals parameters estimation. To estimate the carrier frequency and the subcarrier spacing frequency, two well-known methods are used, which are based on the analysis of the characteristics of the amplitude-frequency spectrum of the radio signal and the instantaneous frequency histogram. To estimate the symbol rate, the method based on the analysis of the cyclostationary properties of the random function of the instantaneous frequency has been improved, and a new method based on the analysis of the peak values of the periodogram has been proposed. The improvement of the first method of symbol rate estimation consists in increasing the probability of correct identification of dominant harmonics in the amplitude-frequency spectrum of the centered normalized instantaneous frequency by preliminary low-pass filtering of the instantaneous frequency, increasing the dimension of the array of its values, and limiting the search band. The second method of symbol rate estimation is based on the search for peak values of the signal periodogram, which arise due to the presence of sections with alternating ones and zeros in the modulation bit sequences. It is shown that the analyzed characteristics have peak values whose frequencies (or frequency difference) are multiples of the symbol rate and frequency deviation. An approach to calculating parameters of frequency shift keying by combining data obtained in four ways is proposed. The efficiency of the method was verified by analyzing the radio signals obtained in the process of computer simulation, as well as real signals of command-telemetry radio lines of the unmanned aerial vehicle.